Effects of ultra-low dose hormone therapy on biochemical bone turnover markers in postmenopausal women: A randomized, placebo-controlled, double-blind trial - Costa-Paiva, Lucia; O Wender, Maria Celeste; Machado, Rogerio B; Pompei, Luciano M; Nahas, Eliana A [UNESP]; Nahas-Neto, Jorge [UNESP]; Del Debbio, Sonia Y; Badalotti, Mariangela; Cruz, Achilles M (Taylor & Francis, 2022)
Objective: Evaluate the effects of ultra-low-dose hormone therapy (Ultra-LD HT) with 17β-estradiol 0.5 mg and norethisterone acetate 0.1 mg (E2 0.5/NETA 0.1) versus placebo on bone turnover markers (BTM) in postmenopausal women. Study Design: A multicenter, double-blind, randomized, placebo-controlled study was performed with 107 participants who received one tablet daily of E2 0.5/NETA 0.1 or placebo for 24-weeks. Bone formation markers-N-terminal propeptide of type I procollagen (PINP) and Bone-specific alkaline phosphatase (BSAP), and bone resorption markers-C-telopeptide of type I collagen (CTX-I) and N-telopeptide crosslinked of type I collagen (NTX) were assessed before and at 12 and 24-weeks of treatment. Results: Women treated with E2 0.5/NETA 0.1 had a significant reduction in the PINP marker from baseline (58.49 ± 21.12 μg/L) to week 12 (48.31 ± 20.99 μg/L) and week 24 (39.16 ± 16.50 μg/L). Placebo group, the PINP marker did not differ significantly. The analysis of the BSAP indicated a significant increase in the placebo group (13.8 ± 5.09 μg/L and 16.29 ± 4.3 μg/L, at baseline and week 24, respectively), whereas in the treatment group the values did not change. The analysis of the NTX marker showed a significant reduction only in the treatment group (43.21 ± 15.26 nM/mM and 33.89 ± 14.9 nM/mM, at baseline and week 24, respectively). CTX-I had a significant decrease in the treatment group from baseline (0.3 ± 0.16 ng/L) to week 12 (0.21 ± 0.14 ng/L) and week 24 (0.21 ± 0.12 ng/L). Conclusion: Women receiving E2 0.5/NETA 0.1 experienced reductions in bone resorption and formation markers, an expected effect during the anti-resorptive therapy, suggesting a protective bone effect with the Ultra-LD HT.
Keywords: bone mineral density; bone turnover marker; estrogen; menopause; ultra-low-dose hormone therapy